Educação matemática em escolas inclusivas: a sala de recursos em destaque - Hilsdorf, Carla Regina Riani [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
This dissertation presents a research based on the question: What are the demands and potentials of working in a resource room by the time of teaching mathematics in inclusive schools? The study was conducted in a primary school, and aimed to investigate possibilities of teachers working at the resource room during the process of teaching and learning mathematics for children with special needs. Counting problems were used as a resource for intervention, which had been worked previously at the resource room in individual sessions, and later at the classroom with the students. We chose to do an intervention that could approach an ideal situation, previously introducing a math content in individualized sessions in a resource room that would later be worked into the regular classroom. That was done with included students, properly diagnosed and who were seen, at a health facility, by various specialists aiming the best development of their skills. Data were obtained through filming, photos and notes, besides interviews with inclusion classes' teachers. The analysis indicated that the way the intervention was performed resulted in several potentialities for the development of the children, amid them, the importance of dialogic situation as mediation and, showing that the difficulties presented by the students are working tools for the resource room teacher, as he or she can understand their needs and work towards meeting them. Tied to this fact the results indicated several demands for the resource room teacher as the importance of planning activities and work in partnership with teachers of regular classes. Based on what has been seen about the students during this study, and established contact with the inclusion classes' teachers, it was observed that it is possible for the teacher from the resource room to create math education environments that are inclusive and motivating, providing to the regular class teacher ideas and resources in...

Esta dissertação apresenta uma pesquisa norteada pela pergunta: Quais são as demandas e potencialidades do trabalho em sala de recursos no âmbito do ensino de matemática em escolas inclusivas? O estudo realizado em uma escola de ensino fundamental teve como objetivo investigar possibilidades de atuação do professor na sala de recursos, no processo de ensino e de aprendizagem de matemática de crianças com deficiências. Foi organizada uma intervenção em que problemas de contagem foram trabalhados anteriormente na sala de recursos em atendimentos individuais e, posteriormente, na sala de aula junto com os alunos da classe. Optou-se por uma intervenção que se aproximasse de uma situação ideal, introduzindo previamente um conteúdo em atendimento individualizado na sala de recursos, que depois seria trabalhado na classe comum. Isso foi feito com alunas de inclusão devidamente diagnosticadas e que eram atendidas numa unidade de saúde em diversas especialidades visando o melhor desenvolvimento de suas habilidades. Os dados foram obtidos através de filmagem, fotos e anotações, além de entrevistas feitas com professoras das classes. A análise dos resultados indicou que a forma como a intervenção foi realizada gerou várias potencialidades para o desenvolvimento das crianças, entre elas, a importância da situação dialógica como mediação e que as dificuldades apresentadas são um instrumento de trabalho para o professor de sala de recursos, pois ele então tem como intervir com os alunos com deficiências naquilo em que eles precisam. Atrelados a este fato os resultados indicaram várias demandas para o professor da sala de recursos como a importância do planejamento das atividades e do trabalho em parceria com as professoras das classes comuns. Com base em tudo o que foi visto com as alunas durante este estudo e no contato estabelecido com as professoras das classes, foi observado que é possível que o professor de sala de...
Keywords: Mathematics - Study and teaching; Matemática - Estudo e ensino; Inclusão em educação; Crianças deficientes - Educação; Material didático